2012
DOI: 10.1002/ccd.24408
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of clinical outcomes for thrombectomy devices with different mechanisms in hemodialysis arteriovenous fistulas

Abstract: For the salvage of thrombosed AV fistulas, a device using rotational mechanism is more time-saving with a higher immediate success rate and secondary patency rate. However, the long-term patency results were not different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 24 publications
2
54
1
3
Order By: Relevance
“…The primary patency rates after 6 months were 45 % with the use of the angio-jet and 43 % after PTD. The secondary patency rates after a year were 74 % and 87 %, respectively [76]. In total, the treatment of the underlying stenosis determines the long-term success of thrombectomy or thrombolysis.…”
Section: Thrombosed Av Fistulamentioning
confidence: 99%
“…The primary patency rates after 6 months were 45 % with the use of the angio-jet and 43 % after PTD. The secondary patency rates after a year were 74 % and 87 %, respectively [76]. In total, the treatment of the underlying stenosis determines the long-term success of thrombectomy or thrombolysis.…”
Section: Thrombosed Av Fistulamentioning
confidence: 99%
“…The outcomes might be hampered by the use of an older AngioJet™ system with lower power and lacking a standardized treatment protocol and expertise. More recent studies, including ours, were conducted with the newer, more powerful, AngioJet™ AVX system and show improved results, reporting clinical success rates of up to 97% …”
Section: Discussionmentioning
confidence: 85%
“…Only two patients in each group did not receive adjuvant periprocedural interventions. It has also been suggested that long‐term patency is dependent on effective treatment of underlying stenosis and not on the thrombectomy technique …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technical and clinical success rates of the various percutaneous declotting techniques range from 75% to 95% in the contemporary literature (14,15). Performing the declotting procedure completely percutaneously has several benefits.…”
Section: Discussionmentioning
confidence: 99%